Optimalisasi Fuzzy Logic System Dalam Identifikasi Kematangan Buah Semangka - Maman; Mochammad Darip (PPPM Institut Teknologi Pagar Alam, 2026)
In watermelon cultivation, determining the right time to harvest is very important because it will affect the quality and selling value. Generally, farmers use various methods to determine the ripeness of watermelon, such as observing changes in skin color, tapping the fruit to listen to the sound it makes, and estimating the age of harvest based on the planting date. Although these methods have been used for many years by farmers, they rely heavily on experience and intuition, which can result in high variability and uncertainty in determining maturity. Modern technological developments offer more scientific and accurate solutions. One approach that can be used is to use fuzzy logic. Fuzzy logic is a computational method that is able to handle uncertainty and imprecision, which is very suitable for applications in the agricultural sector where many variables are difficult to measure with certainty. This research will examine how harvest age and tapping sound can be integrated in a fuzzy logic system to determine the ripeness of watermelon more scientifically and accurately. The research results show that the implementation of the fuzzy logic system in optimizing the identification of watermelon ripeness was successfully integrated into a programming language to produce a software with fuzzy algorithm method stages based on two parameter variables, namely harvest age and the sound produced when a watermelon is tapped (decibels).